Analysis of Past and Present Landscapes Surrounding the Necropolis of Dahshur - Bebermeier, Wiebke; Alexanian, Nicole; Blaschta, Dirk; Ramisch, Arne; Schütt, Brigitta; Seidlmayer, Stephan Johannes (DIE ERDE – Journal of the Geographical Society of Berlin, 2011)
The landscape evolution of the area surrounding the necropolis of Dahshur (Egypt) is analysed on the basis of geomorphological investigations and the integration of late Holocene sediment characteristics. Knowledge of the ancient landscape and palaeoenvironmental conditions allows a better understanding of spatial relationships between monuments and landscape. From altogether 41 sondages conducted mainly by archaeologists of the German Archaeological Institute (DAI), we selected eight sondages along three transects and one single sondage. Furthermore, the results of geomorphometrical analysis will be presented. The chosen sondages are characteristic of the typical landscape units of the study area: floodplain of the river Nile, limestone escarpment of the Western Desert and the desert margins east of the escarpment scarp. The geomorphology and channel geometry were also analysed. The results show that different processes influenced the relief of the study area. From the late Old Kingdom onwards, aeolian dynamics levelled the landscape mainly in the channel beds and in the desert margin east of the escarpment scarp. Human activities such asmining in the period of the Old Kingdom also shaped the relief. Depressions situated in a semicircularform around the Bent Pyramid are interpreted as quarries and give evidence of this activity.